Stock Price Valuation Analysis for Investment Decision Making in PT Telkom Before and During Covid-19 - Rika Kartika; Ibrohim Ibrohim; Ulfi Jefri; Vina Purwasih (Jurnal Riset Akuntansi Terpadu, 2022)
Investors' decisions in terms of selling or buying shares, on average, are more concerned with the company's profit performance. This study was conducted to determine the intrinsic value of shares and the ratio of book value per share of TLKM for the period 2016-2020. The analytical tools used are the Dividend Discount Model (DDM), Price Earning Ratio (PER) and Price to Book Value (PBV). In this study using qualitative methods with secondary data, namely the financial statements of PT TLKM. The results of the study show that the intrinsic value of TLKM shares assessed using the DDM and PER approaches resulted in the same condition, namely overvalued in the pre-covid-19 period (2016-2019), except in 2018 in the undervalued category. Meanwhile, during the Covid-19 (2020) period, TLKM shares were in the undervalued category. The results showed that the right decision during the covid-19 period was buying TLKM shares. The novelty in this research is to analyze stock price valuation through intrinsic value and book value.Keywords: Dividend Discount Model; Price to Book Value; Price  Earning Ratio; Stock Price